Pengaruh Model Pembelajaran Kooperatif Tipe Student Teams Achievement Divisions (STAD) Terhadap Kemampuan Berpikir Kritis pada Materi Aritmetika Sosial Kelas VII - Afifatu Ayu Khoiru Umah; Nanang Nabhar Fakhri Auliya (Lembag, 2026)
Students’ low critical thinking skills in mathematics remain a persistent issue, largely due to teacher-centered instructional practices that limit student participation and hinder deep conceptual understanding. To address this problem, a more engaging learning approach is required, such as the Student Teams Achievement Divisions (STAD) cooperative learning model. This study aims to examine whether students taught using the STAD model demonstrate higher critical thinking abilities than those taught through direct instruction in social arithmetic topics. The research employed an experimental method with a quantitative approach, using a posttest-only control group design. The sample consisted of two classes: an experimental group and a control group. Data were collected through essay-based tests designed to measure students’ critical thinking skills. The analysis involved prerequisite testing and hypothesis testing using an independent sample t-test. The findings revealed that the calculated t-value (2.033) exceeded the t-table value (2.00958) at a 0.05 significance level, indicating a significant difference. Therefore, the STAD model proves more effective in enhancing students’ critical thinking skills.